SOSIALISASI PENGELOLAAN SAMPAH DAN PENGADAAN BANK SAMPAH DI SEKOLAH DASAR NEGERI 3 RENON - Kadek Aulya Ari Maharani Swibawa; I Putu Dharmawan Pradhana; Ni Putu Yunita Anggreswari; Nyoman Sri Manik Parasari; Anak Agung Istri Agung Maheswari (Bajang Institute, 2025)
Waste management can be done with 3R principle (Reduce, Reuse, Recycle), which is simple waste management, which can carried out independently at individual or village level, in Renon Village which already has waste bank. referring to the problem, case of lack knowledge waste management and existence of waste banks by students at SDN 3 Renon. The purpose, this activity is importance of increasing environmental awareness at SDN 3 Renon through implementation, socialisation of waste management and influence existence waste banks. The method of implementing this activity is in form of socialisation with lecture methods and simple delivery. The results this activity showed enthusiasm from students and enthusiasm to sort waste according to its type so as to reduce waste and submit it to the waste bank. It was concluded that socialisation carried out had positive impact on increasing students' knowledge 3R principles and existence of waste banks for environment